2016
DOI: 10.1038/srep21785
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Fluorescence (NIRF) Molecular Imaging of Oxidized LDL with an Autoantibody in Experimental Atherosclerosis

Abstract: We aimed to develop a quantitative antibody-based near infrared fluorescence (NIRF) approach for the imaging of oxidized LDL in atherosclerosis. LO1, a well- characterized monoclonal autoantibody that reacts with malondialdehyde-conjugated LDL, was labeled with a NIRF dye to yield LO1-750. LO1-750 specifically identified necrotic core in ex vivo human coronary lesions. Injection of LO1-750 into high fat (HF) fed atherosclerotic Ldlr−/− mice led to specific focal localization within the aortic arch and its bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…OxLDL, acetylated LDL, MMPs). Recently for example, Khamis et al (67) developed an antibody-based NIRF approach for targeting oxLDL in vivo – providing new potential avenues for exploring molecular compositions of atheroma longitudinally with intravascular NIRF imaging.. In addition, FDA-approved indocyanine green is a promising translational NIR fluorophore for plaque imaging (68), and has recently been shown to report on impaired endothelial barrier function in human plaques (69).…”
Section: Introductionmentioning
confidence: 99%
“…OxLDL, acetylated LDL, MMPs). Recently for example, Khamis et al (67) developed an antibody-based NIRF approach for targeting oxLDL in vivo – providing new potential avenues for exploring molecular compositions of atheroma longitudinally with intravascular NIRF imaging.. In addition, FDA-approved indocyanine green is a promising translational NIR fluorophore for plaque imaging (68), and has recently been shown to report on impaired endothelial barrier function in human plaques (69).…”
Section: Introductionmentioning
confidence: 99%
“…They represent danger-associated molecular patterns and induce a proinflammatory response (14,15). Additionally, prior work has shown that OSEs can be imaged in zebrafish, mice, and rabbit lipid/atherosclerosis models with murine or human OSE-targeted antibodies using nuclear and magnetic resonance (MR) imaging techniques (1622). However, the potential immunogenicity of these approaches may limit clinical application (23,24).…”
mentioning
confidence: 99%
“… 7 Near-infrared fluorescence (NIRF) optical molecular imaging offers a new approach to the evaluation of coronary plaque biology, especially helped by the development of intravascular NIRF detectors. 8 , 9 Compared to the use of radionuclear reporters, intravascular NIRF targeting would have the advantage of not adding radiation as well as providing better spatial resolution compared to whole-body approaches. The ultimate goal of NIRF molecular targeting is to integrate specific multi-agent biological information with morphological imaging obtained by existing catheter-based technologies (ie, IVUS and OCT), thereby providing a much needed extra dimension for improving the prediction of individual plaque progression and instability.…”
mentioning
confidence: 99%
“… 19 , 20 As yet, we are the only group to report quantitative optical molecular imaging of oxLDL in atherosclerosis in conjunction with other molecular probes. 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation